Karakteristik Abon Ikan Gabus Dengan Penambahan Limbah Kulit Pisang Kepok: Characteristics of Snakehead Fish Floss with the Addition of Kepok Banana Peel Waste - Evnaweri, Evnaweri; Sulistyaningrum, Tyas Wara; Sianturi, Lastarida (FKIP, Universitas Palangka Raya, 2025)
This research aims to determine the characteristics of snakehead fish floss with the addition of kepok banana peel waste. The experimental design was prepared from 4 treatments and 3 repetitions, namely: A (without the addition of kepok banana peel), B (with the addition of 75 grams of kepok banana peel), C (with the addition of 100 grams of kepok banana peel) and D (with the addition of 125 grams of kepok banana peel kepok banana). The data collected is based on the results of tests carried out objectively (chemical tests) including tests for water content, protein and fiber content. The addition of kepok banana peel waste to snakehead fish floss has a significant effect on good water and protein content, as well as contributing to the fiber content of snakehead fish floss. The addition of 75 grams of kepok banana peel from the weight of 250 pieces of snakehead fish meat gives a different character from normal shredded meat.